Revision of Chinese Dilaridae (Insecta: Neuroptera) (Part III): Species of the genus Dilar Rambur from the southern part of mainland China - Zhang, Wei; Liu, Xingyue; Aspöck, Horst; Aspöck, Ulrike (Zootaxa, 2015)
A revision of species of the genus Dilar Rambur, 1838, from the southern part of mainland China is presented. Twenty species are recorded in this region, with 12 species described as new to science. Dilar spectabilis Zhang, Liu, H. Aspöck & U. Aspöck, 2014, is recorded in this region for the first time. The other seven valid species previously recorded in this region are re-described. Dilar wangi Yang, 1992, is herein treated as a junior synonym of Dilar montanus Yang, 1992. A key to all species of the genus Dilar so far recorded from China is provided.